In vitro digestion of edible nanostructured lipid carriers: Impact of a Candelilla wax gelator on performance - Sislioglu, Kubra; Gumus, Cansu Ekin; Koo, Charmaine K. W.; Karabulut, Ihsan; McClements, David Julian (Elsevier, 2021)
In this study, food-grade nanostructured lipid carriers (NLCs) were used as delivery systems to overcome some of the limitations of solid lipid nanoparticles (SLNs) and liquid lipid nanoparticles (LLNs). Organogel NLCs were prepared using an oil phase consisting of a hydrophobic gelator (Candelilla wax) dispersed in liquid corn oil. The oil phase undergoes a gel-to-sol transition when heated, which means that oil-in-water nanoemulsions can be used as templates to form the NLCs. The impact of lipid phase composition on the gastrointestinal fate of the NLCs was determined using a simulated gastrointestinal tract (GIT). The particle size, zeta-potential, and microstructure of the LLNs, NLCs and SLNs were characterized when they were exposed to model oral, gastric, and small intestine conditions. The oil phase in the LLNs and SLNs consisted of pure corn oil and pure Candelilla wax, respectively. Initially, all samples contained small lipid particles (d(43) = 150-202 nm) with negative surface potentials (zeta = -26 to -47 mV). The LLNs, SLNs and NLCs behaved similarly in the simulated GIT in terms of their particle properties: there was a large increase in particle size and decrease in charge magnitude in the mouth, stomach, and intestine. The Candelilla wax in the SLNs and NLCs was not digested by lipase, but the corn oil in the LLNs and NLCs was fully digested. This phenomenon may be used to create colloidal delivery systems that can control the release of encapsulated bioactive agents within the GIT.
Keywords: Organogel; Nano-structured; Lipid carrier system; Candelilla wax; In vitro digestion